ผลของซิลิกอนจากอุตสาหกรรมซีเมนต์ต่อการเจริญเติบโตและผลผลิตของข้าวพันธุ์ปทุมธานี 1 ภายใต้ระดับการให้น้ำที่แตกต่างกัน - วัฒนเดชเสรี เวธนี; ชคตระการ สมชาย; ภูมิพันธ์ พักตร์เพ็ญ; ชุติมานุกูล พฤกษ์ (Thai Journal of Science and Technology, 2019)
Abstract Drought is considered to be a serious factor limiting rice production and quality. The objective of this study was to determine suitable amount of silicon application in soil for growth and yield and the effect of silicon on the resistance to drought stress of rice cv. Pathum Thani 1 under different water supply. A pot experiment was undertaken in factorial in CRD with 12 replications. The study factors were (1) different levels of water supply, corresponding to 100 (normal condition or control), 50, 25 and 12.5 % of full water supply, and (2) different levels of silicon, corresponding to 0, 50, 150, 300 and 500 kg/rai. The results showed that decreased water level as a result, the growth and yield components of rice decreased when comparing to those of the control. In addition, different levels of silicon also influenced both growth and yield of rice cv. Pathum Thani 1. Silicon at 300 kg/rai increased growth (plant height, root dry weight, shoot dry weight, tiller number per plant, photosynthetic rate, transpiration rate and stomatal conductance) and yield components (panicle number per plant, filled grains per panicle, 100 grain weight and yield per plant) of rice cv. Pathum Thani 1 when compared with other silicon level and it also reduced the undeveloped grains per panicle as a result, the productivity increases. It was, therefore, concluded that 300 kg/rai of silicon reduced the effect of toxicity from drought stress to rice cv. Pathum Thani 1 and it was also suitable for the growth and yield of rice cv. Pathum Thani 1. Keywords: growth; rice cv. Pathum Thani 1; silicon; yield; level of water supply